Synthesis and antifungal activity of (Z)-5-arylidenerhodanines - Sortino, Maximiliano Andrés (2007)
An efficient microwave-assisted synthesis of new (Z)-5-arylidenerhodanines under solvent-free conditions is described and their in vitro antifungal activity was evaluated following the CLSI (formerly NCCLS) guidelines against a panel of both standardized and clinical opportunistic pathogenic fungi. An analysis of the structure-activity relationship (SAR) along with computational studies showed that the most active compounds (F- and CF3-substituted rhodanines) possess high log P values and low polarizability. Mechanism-based assays suggest that active compounds neither would bind to ergosterol nor would produce a damage to the fungal membrane.